Developing an Android-Based Reader Digital Application to Teach Reading Aloud at SMPN 7 Blitar - Dian Aprilia Briliani; Widiarini Widiarini; Istina Atul Makrifah (Universitas Pendidikan Mandalika, 2023)
Students in junior high school, especially in 7th grade are commonly taught reading aloud on learning English. Based on those reasons, research on developing an android-based reader digital application is really needed to be conducted because technology could create productive and interesting teaching and learning process. The purposes of the study are to find out the process of developing an android-based reader digital application as media to teach reading aloud in 7th grade at SMPN 7 Blitar and to figure out the feasibility of an android-based reader digital application as media to teach reading aloud in 7th grade at SMPN 7 Blitar. In order to develop the product Research and Development (R&D) method by Borg and Gall contained 10 steps was used. And it is reduced to 7 steps because of the seven steps can be developed in the product and there is limited time. The observation did by questionnaires. A technique for collecting data from multiple validator experts. Effectiveness is derived from the results of student surveys. The results of this survey show that the materials expert's overall score was 93.8% and 90% for display layout and design by media professionals. Data collection for a survey of 30 students was also 85%. The result shows that the use of applications in he English learning process is approved by teachers and students. The students also sense more motivated to learn English through the application and show an attractive to use the application as the virtual teacher assistant.